Neutral ceramidase is a marker for cognitive performance in rats and monkeys - Kalinichenko, Liubov; Wang, An Li; Mühle, Christiane; Abdel-Hafiz, Laila; Gulbins, Erich; Kornhuber, Johannes; Oliveira, André W.C.; Barros, Marilia; Huston, Joseph P.; Müller, Christian P. (Pharmacological Reports, 2020)
Background: Ceramides are lipid molecules determining cell integrity and intercellular signaling, and thus, involved in the pathogenesis of several psychiatric and neurodegenerative disorders. However, little is known about the role of particular enzymes of the ceramide metabolism in the mechanisms of normal behavioral plasticity. Here, we studied the contribution of neutral ceramidase (NC), one of the main enzymes mediating ceramide degradation, in the mechanisms of learning and memory in rats and non-human primates. Methods: Naïve Wistar rats and black tufted-ear marmosets (Callithrix penicillata) were tested in several tests for short- and long-term memory and then divided into groups with various memory performance. The activities of NC and acid ceramidase (AC) were measured in these animals. Additionally, anxiety and depression-like behavior and brain levels of monoamines were assessed in the rats. Results: We observed a predictive role of NC activity in the blood serum for superior performance of long-term object memory tasks in both species. A brain area analysis suggested that high NC activity in the ventral mesencephalon (VM) predicts better short-term memory performance in rats. High NC activity in the VM was also associated with worse long-term object memory, which might be mediated by an enhanced depression-like state and a monoaminergic imbalance. Conclusions: Altogether, these data suggest a role for NC in short- and long-term memory of various mammalian species. Serum activity of NC may possess a predictive role in the assessing the performance of certain types of memory.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Ceramide; Memory; Neutral ceramidase; Non-human primates; Rats; Ventral mesencephalon